Morphological evaluation of silicone/clay slurries by small-angle/wide-angle x-ray scattering - Kaneko,Manuela L. Q. A. (2007)
Silicone/clay slurries were prepared by mechanical blending of different silicone fluids and montmorillonite clays. Two dispersion series containing (1) a natural montmorillonite (MMT) and (2) an organic montmorillonite (O-MMT) were prepared using poly (dimethylsiloxane) with -Si(CH3)2OH end groups (PDMS-OH), poly(dimethylsiloxane-co-methylpropylethylene oxide siloxane) (PDMS-PEO) or a poly(dimethylsiloxane-co-aminoethylaminopropylmethylsiloxane)/water emulsion (PDMS-NH2) as dispersion fluids. The resulting morphology of the silicone/clay slurries was characterized by small-angle/wide-angle X-ray scattering using a two-dimensional imaging plate detector (2D-SAXS/WAXS). The PDMS-OH/clay slurries showed only a slight increase in the layer separation while a more pronounced effect was found for the PDMS-NH2 and PDMS-PEO slurries, which resulted in expanded tactoids. Analyses in the SAXS region also indicated the existence of thin platelets for the MMT slurries prepared with PDMS-NH2 and PDMS-PEO fluids. This hierarchical structure, formed by thin platelets and expanded tactoids, was also found in the O-MMT/silicone slurries.